2010
DOI: 10.1016/s1474-4422(10)70093-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation plus best medical therapy versus best medical therapy alone for advanced Parkinson's disease (PD SURG trial): a randomised, open-label trial

Abstract: SummaryBackgroundSurgical intervention for advanced Parkinson's disease is an option if medical therapy fails to control symptoms adequately. We aimed to assess whether surgery and best medical therapy improved self-reported quality of life more than best medical therapy alone in patients with advanced Parkinson's disease.MethodsThe PD SURG trial is an ongoing randomised, open-label trial. At 13 neurosurgical centres in the UK, between November, 2000, and December, 2006, patients with Parkinson's disease that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
511
5
22

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 659 publications
(552 citation statements)
references
References 33 publications
14
511
5
22
Order By: Relevance
“…Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is very effective for the treatment of patients with advanced Parkinson's disease (PD), improving both motor PD symptoms and levodopainduced motor complications [1]. Some large randomized controlled clinical trials have shown that in the short-term follow-up STN-DBS is superior to best medical treatment alone in controlling motor symptoms and complications and thus improving self-reported quality of life [1], [2] and [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is very effective for the treatment of patients with advanced Parkinson's disease (PD), improving both motor PD symptoms and levodopainduced motor complications [1]. Some large randomized controlled clinical trials have shown that in the short-term follow-up STN-DBS is superior to best medical treatment alone in controlling motor symptoms and complications and thus improving self-reported quality of life [1], [2] and [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some large randomized controlled clinical trials have shown that in the short-term follow-up STN-DBS is superior to best medical treatment alone in controlling motor symptoms and complications and thus improving self-reported quality of life [1], [2] and [3].…”
Section: Introductionmentioning
confidence: 99%
“…After an initial honeymoon period, during which there is a sustained response to dopaminergic treatment, beneficial effects are hampered by levodopainduced motor complications, 1 progressively compromising quality of life. [2][3][4] Because levodopa-responsive parkinsonian symptoms are improved by high-frequency stimulation of the subthalamic nucleus, 5,6 neurostimulation has become an established treatment for advanced Parkinson's disease with medically intractable fluctuations and dyskinesia [7][8][9][10] and has shown long-term efficacy. [11][12][13] It is typically used after the disease has been present for 11 to 13 years, 7-10 when quality of life, social adjustment (psychosocial competence), 14 and professional activity are already severely impaired.…”
mentioning
confidence: 99%
“…[11][12][13] It is typically used after the disease has been present for 11 to 13 years, 7-10 when quality of life, social adjustment (psychosocial competence), 14 and professional activity are already severely impaired. Neurostimulation improves quality of life, [7][8][9][10] in addition to motor symptoms. Moreover, later in the course of the disease, features unresponsive to dopaminergic treatment often predominate.…”
mentioning
confidence: 99%
“…Surgical treatment for PD, in the form of deep brain stimulation (DBS) of the subthalamic nucleus, globus pallidus interna or pedunclopontine nucleus, or lesioning has become an increasingly feasible option [9,10] and cost effective [11]. DBS has been proven in clinical trials to be superior to best medical therapy [12][13][14] and to be more effective in improving quality of life if used earlier in the course of the disease [15]. The effects of surgical therapy on non-motor features are under investigation and some may improve due to the DBS itself and others from a reduced drug burden [16].…”
Section: Current Treatment Strategies For Pdmentioning
confidence: 99%